Computational insight into the origin of unexpected contrast in chiral markers as revealed by STM. Issue 4 (21st December 2017) - Sanz-Matías, Ana; Ivasenko, Oleksandr; Fang, Yuan; De Feyter, Steven; Tahara, Kazukuni; Tobe, Yoshito; Harvey, Jeremy N.
Abstract : Chiral substituents in self-assembled molecular layers show differences in bias dependence in STM image contrast. Abstract : Internal substituents can serve the double purpose of generating stereogenic centers and (potentially) being identifiable with Scanning Tunneling Microscopy (STM) in 2D self-assembled molecular layers. We investigate computationally the origin of stark contrast variations in STM images of chirally substituted self-assembled organic films. STM images of alkyl derivatives with secondary –CH3 and –OH groups have been simulated. Density functional theory calculations reveal bias-dependent contrast reversals in the substituent regions: a lack of local density of states in the relevant energy regime results in 'dark spots' in the simulated STM images, which turn bright upon increasing the bias voltage.